Kombilöhne und Mindestlöhne als Instrumente der Beschäftigungspolitik: Erfahrungen und Handlungsoptionen - Werner Eichhorst (Institute for the Study of Labor (IZA), 2006)
The paper reviews national and international experiences with different combinations of in-work benefits, subsidized employment, statutory minimum wages and implicit minimum wages defined by social assistance provisions. It calls for a cautious approach regarding the introduction of additional minimum wages in Germany and more generous in-work benefits combined with an unchanged level of social assistance.
Keywords: J38; J48; J68; 330; in-work benefits; minimum wages; subsidized employment; Germany; Lohnsubvention; Mindestlohn; Beschäftigungspolitik; Beschäftigungseffekt; Welt; Deutschland